Persistent viremia by a novel parvovirus in a slow loris (Nycticebus coucang) with diffuse histiocytic sarcoma - Canuti, Marta; Williams, Cathy V.; Gadi, Sashi R.; Jebbink, Maarten F.; Oude Munnink, Bas B.; Jazaeri Farsani, Seyed Mohammad; Cullen, John M.; van der Hoek, Lia (Frontiers in Microbiology, 2014)
Cancer is one of the leading health concerns for human and animal health. Since the tumorigenesis process is not completely understood and it is known that some viruses can induce carcinogenesis, it is highly important to identify novel oncoviruses and extensively study underlying oncogenic mechanisms. Here, we investigated a case of diffuse histiocytic sarcoma in a 22 years old slow loris (Nycticebus coucang), using a broad spectrum virus discovery technique. A novel parvovirus was discovered and the phylogenetic analysis performed on its fully sequenced genome demonstrated that it represents the first member of a novel genus. The possible causative correlation between this virus and the malignancy was further investigated and 20 serum and 61 organ samples from 25 animals (N. coucang and N. pygmaeus) were screened for the novel virus but only samples collected from the originally infected animal were positive. The virus was present in all tested organs (intestine, liver, spleen, kidneys and lungs) and in all banked serum samples collected up to 8 years before death. All attempts to identify a latent viral form (integrated or episomal) were unsuccessful and the increase of variation in the viral sequences during the years was consistent with absence of latency. Since it is well known that parvoviruses are dependent on cell division to successfully replicate, we hypothesized that the virus could have benefitted from the constantly dividing cancer cells and may not have been the cause of the histiocytic sarcoma. It is also possible to conjecture that the virus had a role in delaying the tumor progression and this report might bring new exciting opportunities in recognizing viruses to be used in cancer virotherapy.